A wind atlas for Germany and the effect of remodeling - Martin Schneider; André Glücksmann; Anselm Grötzner; Heinz-Theo Mengelkamp (Meteorologische Zeitschrift, 2022)
Minimizing and quantifying the uncertainty of wind simulations are essential for the wind energy industry during the planning phase of wind farm projects and for financial considerations. Measurements at 118 sites onshore and offshore in Germany are analyzed and used for the verification of wind simulations with the mesoscale model WRF. In order to minimize the difference between simulations and observations a correction of the annual cycle is applied and a remodeling approach is developed which allows for a correction of the simulated wind speed time series. The remodeling methodology is based on a linear regression analysis of simulated and observed wind speed time series accounting for sub‑grid variations of orography and roughness. Averaging the regression parameter for 26 measurement sites results in an overall global parameter set which is applied to the wind atlas data. While the “raw” data (without optimization) before any correction showed differences of up to 30 % with respect to the annual mean wind speed the remodeling process reduced the bias to below 5 % for the majority of measurements. When being compared with data from the NEWA wind atlas and the EMD‑WRF Europe+ data set an overall bias between 0.6 m/s and 0.8 m/s is found for the NEWA, EMD‑WRF Europe+ and anemos “raw” data. This bias is reduced to zero with a small standard deviation when the remodeling process and the site-specific adaptation are applied.